The Efficient Regeneration of Corneal Nerves via Tunable Transmembrane Signaling Channels Using a Transparent Graphene‐Based Corneal Stimulation Electrode. Issue 10 (11th February 2022) - Zheng, Zheng; Lin, Mimi; Lu, Weicong; Huang, Pingping; Zheng, Yaru; Zhang, Xincheng; Yan, Lu; Wang, Wei; Lawson, Tom; Shi, Bingyang; Chen, Shihao; Liu, Yong
Abstract: The efficient regeneration of corneal nerves is of limited success in the field of ophthalmology. This work reports the use of a non‐invasive electrical stimulation technique that uses a transparent graphene‐based corneal stimulation electrode and that can achieve efficient regeneration of corneal nerves. The corneal stimulation electrode is prepared using electroactive nitrogen‐containing conducting polymers such as polyaniline functionalized graphene (PAG). This composite can carry a high capacitive current. It can be used to tune transmembrane signaling pathways including calcium channels and the MAPK signaling pathway. Tuning can lead to the efficient regeneration of corneal damaged nerves after the surgery of laser in‐situ keratomileusis (LASIK). The composite and its application reported have the potential to provide a new way to treat nerve‐related injuries. Abstract : Efficient regeneration of corneal nerves is realized by an electrical stimulation via a corneal nanoelectrode. Nitrogen‐containing conducting polymer functionalized graphene is used to improve the electroactivity of the stimulation electrode. The transmembrane signaling pathways including calcium channels and the MAPK pathway are activated to support the regeneration of the damaged trigeminal ganglion neurons after the surgery of laser in situ keratomileusis.